2019
DOI: 10.1186/s12986-019-0390-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between coffee consumption and risk of bladder cancer in a meta-analysis of 16 prospective studies

Abstract: Background Current evidence remains equivocal as to whether and how consumption of coffee may be associated with risk of bladder cancer, and potential influence of confounding by smoking on this association is yet to be elucidated. We conducted an updated meta-analysis of prospective studies to address these issues. Methods Relevant studies were identified by searching PubMed and EMBASE databases from inception to April 2019. A rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Some analyses showed positive association [ 82 , 83 , 84 ], while other analyses demonstrated inverse association [ 85 , 86 ]. Some reports concluded that no statistically significant association was observed [ 13 , 87 ]. A prospective study revealed that positive association between coffee and bladder cancer was attenuated after adjustment for smoking and other potential confounders [ 84 ].…”
Section: Potential Effects Of Environmental Factors On Bladder Canmentioning
confidence: 99%
“…Some analyses showed positive association [ 82 , 83 , 84 ], while other analyses demonstrated inverse association [ 85 , 86 ]. Some reports concluded that no statistically significant association was observed [ 13 , 87 ]. A prospective study revealed that positive association between coffee and bladder cancer was attenuated after adjustment for smoking and other potential confounders [ 84 ].…”
Section: Potential Effects Of Environmental Factors On Bladder Canmentioning
confidence: 99%
“…Case-control study conducted by Yu et al reported the positive association between coffee consumption and bladder cancer among never smokers but not in current smokers [3]. Meta-analysis published by Dai et al reported that to date available evidence was insufficient to support an independent association between coffee consumption and bladder cancer risk [2]. Although, there was an increased risk of bladder cancer related to higher coffee consumption among studies with fewer cases (RR high vs low = 1.38, 95% CI 1.05-1.81), smoking was poorly adjusted among these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, several risk factors were identified for early diagnosis or prevention of this type of cancer. Smoking [ 1 ], coffee consumption [ 2 , 3 ], occupational exposure [ 4 ], and dietary factors [ 5 ] constitute the most important exogenous risk factors for bladder carcinogenesis [ 6 ]. Among these, smoking is the most well-known risk factor for bladder cancer [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study and a meta-analysis found no association between coffee drinking and bladder cancer risk [ 72 ], which was confirmed in a recent meta-analysis of 16 prospective studies [ 135 ]. Likewise, meta-analyses suggest no association or a slightly reduced risk of kidney cancer in coffee drinkers [ 136 , 137 ].…”
Section: Impact Of Coffee On Cancer Risk In Humansmentioning
confidence: 82%